2018
DOI: 10.1055/s-0038-1673365
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CYP3A4 Polymorphism in Sex Steroids as a Risk Factor for Breast Cancer

Abstract: Objective Epidemiological studies have shown evidence of the effect of sex hormones in the pathogenesis of breast cancer, and have suggested a relationship of the disease with variations in genes involved in estrogen synthesis and/or metabolism. The aim of the present study was to evaluate the association between the CYP3A4*1B gene polymorphism (rs2740574) and the risk of developing breast cancer. Methods In the present case-control study, the frequency of the CYP3A4*1B gene polymorphism was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…In comparison with the wild type CYP3A4*1A, CYP3A4*1B shows about a 2-fold increase in enzyme activity [15,16]. However, these data are not uniform, since a decrease in the catalytic activity of the enzyme was also determined [17], or unclear clinical effect was described [18], and some even linked this SNP with increased cancer risk [19,20]. Frequent single nucleotide polymorphism (SNP) of CYP3A5 gene is a substitution of adenine with guanine in intron 3: 6896A>G (rs776746).…”
Section: Introductionmentioning
confidence: 95%
“…In comparison with the wild type CYP3A4*1A, CYP3A4*1B shows about a 2-fold increase in enzyme activity [15,16]. However, these data are not uniform, since a decrease in the catalytic activity of the enzyme was also determined [17], or unclear clinical effect was described [18], and some even linked this SNP with increased cancer risk [19,20]. Frequent single nucleotide polymorphism (SNP) of CYP3A5 gene is a substitution of adenine with guanine in intron 3: 6896A>G (rs776746).…”
Section: Introductionmentioning
confidence: 95%
“…This functional variant, also known as CYP3A4*1B (rs2740574), is known to alter the gene's transcriptional activity and thus the overall activity of CYP3A4. It has been reported to reduce its activity (11). It has been reported that this activity change can lead to serious toxicity or therapeutic failure by altering the relationship between dose and blood concentration of the pharmacologically active drug by affecting the metabolic rate of drugs (10).…”
Section: Introductionmentioning
confidence: 99%